Tibia length is an appropriate standard for evaluating hypertrophy in streptozotocin-induced diabetic complications - Qin, Miao; Shao, Feng; Fernandez, Teresa; Wang, Yixin; Wieland, Thomas; Vettel, Christiane; Feng, Yuxi (Naunyn-Schmiedeberg's archives of pharmacology, 2025)
The pathogenesis of diabetic complications has been extensively studied in streptozotocin (STZ)-induced diabetic mice. Body weight (BW) is still used to standardize organ hypertrophy, but it may be unreliable due to significant weight loss in this model. This study aimed to assess the reliability of using tibia length (TL) as a common standard for organ hypertrophy in emaciated diabetic mice. Diabetes was induced by STZ in wild type mice with C57BL6/N (6N) and BL6/J (6J) background. TL and the weights of the heart (HW), kidneys (KW), and bladder (BLW) were estimated at 1-, 3-, and 6-month post-diabetes induction. The 6N mice were more sensitive to STZ than the 6J mice. In 1-month diabetic mice, the HW, HW/TL, and HW/TL3 ratios decreased in both substrains. In contrast, BLW/TL and BLW/TL3 ratios increased in the 6J but not in the 6N mice, suggesting that the 6J is more suitable for early-stage diabetic bladder research. In 3-month diabetic mice, KW/TL and KW/TL3 ratios significantly increased in the 6J mice, suggesting that the 6J strain is more appropriate for studying early-stage diabetic nephropathy. In 6-month diabetic mice, both substrains were comparable. Interestingly, in non-diabetic 6-month 6N mice, HW, KW, and TL were positively correlated with BW, while in non-diabetic 6J mice, TL and TL3 were consistently correlated positively with HW. TL is a more reliable metric for indexing organ hypertrophy in emaciated diabetic mice. Additionally, the C57BL/6J substrain is more appropriate than C57BL/6N for studying early-stage diabetic nephropathy and cystopathy.